2021
DOI: 10.1021/acs.energyfuels.0c04359
|View full text |Cite
|
Sign up to set email alerts
|

Isotherm, Kinetic, Process Modeling, and Techno-Economic Analysis of a Diamine-Appended Metal–Organic Framework for CO2 Capture Using Fixed Bed Contactors

Abstract: Diamine-appended metal-organic frameworks exhibiting step-shaped CO2 adsorption are exceptional candidates for energy-efficient carbon capture. However, there are few studies examining their performance in real-world capture scenarios, in part due to the challenge inherent in modeling their CO2 uptake behavior. Here, we develop a dual-site Sips model to fit experimental CO2 adsorption data for dmpn-Mg2(dobpdc) (dmpn = 2,2-dimethyl-1,3-diaminopropane; dobpdc 4-= 4,4′-dioxidobiphenyl-3,3′-dicarboxylate) and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 33 publications
3
59
0
Order By: Relevance
“…Alternatively, amine-appended MOFs have shown notable promise for CO 2 capture. However, the path to commercialization of amine-appended MOFs is still evolving; these materials have poor thermal conductivity that requires substantial heat management in the adsorption bed ( 34 ) with uncertain material scale-up costs ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, amine-appended MOFs have shown notable promise for CO 2 capture. However, the path to commercialization of amine-appended MOFs is still evolving; these materials have poor thermal conductivity that requires substantial heat management in the adsorption bed ( 34 ) with uncertain material scale-up costs ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ntouros et al 130 adopted the LCA to investigate and evaluate the five synthetic routes for the production of ZIF-8 and found that deionized water as a solvent was more environmentally friendly than DMF and methanol. Hughes et al 131 investigated “basic” (no bed cooling during adsorption) and “modified” (bed cooling during adsorption) temperature swing adsorption (TSA) processes using dmpn-Mg 2 (dobpdc), respectively, and compared their process economics to the most advanced MEA capture systems. This showed that both sorbent-based TSA processes were expected to cost less than the MEA systems due to 85% heat recovery.…”
Section: Application Of Mofs For Co2 Capturementioning
confidence: 99%
“…Moreover, in the special case of 2-ampd-appended-Mg 2 (dobpdc), the nonisothermal operation typically associated with packed beds increases the cost of the separation process. 19 Indeed, active thermal management (i.e., cooling during adsorption) has been identified as a critical aspect in the development of sorbents with type V isotherms. 19 To develop amine-functionalized MOFs for future implementation and commercialization, an alternative approach is needed.…”
Section: Introductionmentioning
confidence: 99%